2016
DOI: 10.1095/biolreprod.116.139261
|View full text |Cite|
|
Sign up to set email alerts
|

Reactive Oxygen Stimulation of Interleukin-6 Release in the Human Trophoblast Cell Line HTR-8/SVneo by the Trichlorethylene Metabolite S-(1,2-Dichloro)-L-Cysteine

Abstract: Trichloroethylene (TCE) is a common environmental pollutant associated with adverse reproductive outcomes in humans. TCE intoxication occurs primarily through its biotransformation to bioactive metabolites, including S-(1,2-dichlorovinyl)-l-cysteine (DCVC). TCE induces oxidative stress and inflammation in the liver and kidney. Although the placenta is capable of xenobiotic metabolism and oxidative stress and inflammation in placenta have been associated with adverse pregnancy outcomes, TCE toxicity in the plac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
36
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 56 publications
7
36
0
Order By: Relevance
“…Although few data are available on the effects of water contaminants and placental function, limited evidence from in vitro investigations suggests potential consequences. Results from one study by Hassan et al (2016) reported that a bioactive intermediate of TCE increased pro-inflammatory cytokines, leading to disruptions in trophoblast functions necessary for placental development. However, concentrations used in the study by Hassan et al (2016) were a magnitude higher than the US EPA’s maximum contaminant level standard for drinking water for TCE.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although few data are available on the effects of water contaminants and placental function, limited evidence from in vitro investigations suggests potential consequences. Results from one study by Hassan et al (2016) reported that a bioactive intermediate of TCE increased pro-inflammatory cytokines, leading to disruptions in trophoblast functions necessary for placental development. However, concentrations used in the study by Hassan et al (2016) were a magnitude higher than the US EPA’s maximum contaminant level standard for drinking water for TCE.…”
Section: Resultsmentioning
confidence: 99%
“…Results from one study by Hassan et al (2016) reported that a bioactive intermediate of TCE increased pro-inflammatory cytokines, leading to disruptions in trophoblast functions necessary for placental development. However, concentrations used in the study by Hassan et al (2016) were a magnitude higher than the US EPA’s maximum contaminant level standard for drinking water for TCE. Chen et al (2004) examined bromodichloromethane, a trihalomethane, and found that exposure disrupted syncytiotrophoblast formation.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, previous in vitro data about the cross-talk of HTR-8/SVneo and healthy hUMSCs was related to the influence of migratory and invasive abilities of the former [29]. We have chosen HTR-8/SVneo cell line basing on the role of early pregnancy extravillous cytotrophoblasts on spiral artery remodeling [57] and its relation to the generation of oxidative stress [58,59]. Our study is the first to examine the cross-talk HTR-8/SVneo and hUMSCs from pathologic pregnancies with regard to cell viability under gestational endocrine stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…Together with serum deprivation, it triggers an increase in necrotic cell death, which was able to be rescued by relaxin, an insulin superfamily hormone expressed by the maternal reproductive system. It has also been shown that trichloroethylene (TCE) or flame retardants such as Polybrominated diphenyl ethers (PBDE, such as BDE-47) do indeed modify the response to oxidative stress in this model [ 30 , 31 ]. The TCE metabolite DCVC (S-(1,2-dichlorovinyl)-l-cysteine) induces inflammation by releasing IL-6 following the generation of ROS, as a result of its disrupted mitochondrial function.…”
Section: Cellular Sources Of Oxidative Stress In the Human Placentmentioning
confidence: 99%